Effect of untethering on occult tethered cord syndrome: a systematic review. (3rd September 2022) - Rezaee, Hamid; Keykhosravi, Ehsan
Abstract: Background and objectives: Despite the evident clinical, neurological, orthopedic, and urodynamic dysfunctions, neuroanatomic imaging is normal in patients with occult tethered cord syndrome (OTCS). Therefore, the diagnosis of OTCS can be very complex. In this regard, this systematic review aimed to determine the main clinical features (i.e. neurological, musculoskeletal, and urological abnormalities) and improvement rates of these symptoms in patients with OTCS after the section of the filum terminale (SFT). Materials and methods: All the papers published in three electronic databases, namely Google Scholar, PubMed, and Web of Science, were searched for the purposes of this study. The searching process started on 15 October and lasted until 9 November 2020. Eventually, 10 reports were found about the clinical outcomes of SFT for the management of the OTCS. Results: The included studies were carried out on a total of 234 patients with OTCS, all of whom had undergone SFT. Evaluation of urologic symptoms revealed that 40–100% of patients with OTCS suffered from urinary instability. Moreover, its improvement rate after SFT was estimated at 59–100%. Evaluation of neurological symptoms indicated that 25–69% of patients with OTCS suffered from back/leg pain, And its improvement rate, the symptoms of back/leg pain of all patients were resolved or improved after SFT. Lower extremity weakness was found in 9–40% of patients with OTCS which was resolved or improved after SFT in about 25–100% of patients. Nevertheless, surgical indications for occult tight filum terminale syndrome remain controversial. Conclusion: Although it seems that the SFT in OTCS patients is promising in treating neurologic, orthopedic and urological symptoms, usage of surgical untethering for patients with OTCS is a controversial issue. Clinical evaluation and urodynamic testing can be used to identify patients with OTCS. However, a multidisciplinary diagnostic work-up is strongly recommended for every child with OTCS.